Alfabetização científica em um contexto de pandemia : a abordagem do sistema imunológico no ensino médio - Santos, Joice Francianny Melo dos (2021)
Science teaching from a Scientific Literacy (SL) perspective aims, among other objectives, to promote discussions that contributes to the formation of reflexive and critical citizens, active participants in society. These principles aimed at the integral formation of the student are pointed out in the official documents that regulate Brazilian basic education. However, the need for SL has become even more evident nowadays, with the world marked by the pandemic caused by the “new coronavirus”. This pandemic causes global changes, especially with regard to social relationships, and was responsible for a high rate of contamination and deaths. In this context, several biology contents about the specific immune system, such as “virology”, “immune system” and “immunization”, were widely present in the media. However, several false news about treatment and prevention strategies, in addition to adverse effects and damages of vaccination, were disseminated in the media and social networks. Given this scenario, this research seeks to investigate the potential and limitations of the approach of contents related to the immune system for the scientific literacy of Brazilian high school students. This work presented a qualitative nature, with a documentary and bibliographic approach. Initially, a bibliographic survey was carried out, in the form of a state of the art, seeking to understand the scenario of research that addresses the teaching of immunology in Brazilian education. Afterwards, the approach of the immune system in biology textbooks (LDs), approved by the PNLD/2018, and the possible contributions of this content to SL, was verified using an evaluative tool for critical scientific education. Among the results obtained, a small amount of publications on the subject was found, reinforcing the need for more research and academic productions on the topic that could make it, and its implications, more clearly understandable and relevant to students. About the textbooks analyzed in this research, there was a presentation of the contents related to the immune system dispersed in several volumes of the collections, leading to a fragmented approach to the subject. In these books, scientific knowledge was presented, in general, in a decontextualized way and without articulation with the scientific literacy. In view of these results, a didactic sequence was elaborated, seeking to overcome the deficiencies found. It is concluded that this research can stimulate scientific production in the area of biology and the improvement of the approach of immunology contents High School classes, making it more relevant to face the challenges that the pandemic presents to us.